Electron momentum spectroscopy of aniline taking account of nuclear dynamics in the initial electronic ground state. (17th March 2016) - Farasat, M; Shojaei, S H R; Morini, F; Golzan, M M; Deleuze, M S
Abstract: The electronic structure, electron binding energy spectrum and (e, 2e) momentum distributions of aniline have been theoretically predicted at an electron impact energy of 1.500 keV on the basis of Born–Oppenheimer molecular dynamical simulations, in order to account for thermally induced nuclear motions in the initial electronic ground state. Most computed momentum profiles are rather insensitive to thermally induced alterations of the molecular structure, with the exception of the profiles corresponding to two ionization bands at electron binding energies comprised between ∼10.0 and ∼12.0 eV (band C) and between ∼16.5 and ∼20.0 eV (band G). These profiles are found to be strongly influenced by nuclear dynamics in the electronic ground state, especially in the low momentum region. The obtained results show that thermal averaging smears out most generally the spectral fingerprints that are induced by nitrogen inversion.